Rational design of enzyme-nanomaterials - Kumar, Challa V. (Challa Vijaya) (Methods in enzymology, 2016)
Rational Design of Enzyme-Nanomaterials, the new volume in the Methods in Enzymology series, continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in rational design of enzyme-nanomaterials, and includes sections on such topics as conjugation of enzymes and dextran-aldehyde polymers, improved activity of enzymes bound to titanate nanosheet, nano-layered 'stable-on-the-table' biocatalysts and nanoparticle-based enzyme sensors.